Effect of hypoxia, normoxia and hyperoxia conditions on gill histopathology in two weight groups of beluga (Huso huso) - Bagherzadeh Lakani, F.; Sattari, M.; Sharifpour, I.; Kazemi, R. (2013)
The influence of dissolved oxygen concentration on gill histopathology of great sturgeon (Huso huso) was evaluated in two weight classes (initial weight 280.9±49.2 g and 1217.9±138.1 g respectively). Oxygen treatments included hypoxia (2-3 mg/l), normoxia (5-6 mg/l) and hyperoxia (9-10 mg/l). The fish were acclimated to experimental tanks for one week then randomly distributed into 9 tanks in each of the initial weight classes (3 and 6 fish per tank in higher and lower initial weight classes respectively) for 8 weeks. In order to find the histopathological changes, gill samples were collected, dehydrated through ethanol series, embedded in paraffin , sectioned at 7 µm thickness using a Leitz microtome and stained with H & E. No mortality was observed over the 8 weeks of the experimental period. There were significant differences in weight and feed intake between treatments in the both weight classes (P<0.05). Fork length showed significant differences in lower initial weight class (P<0.05). The main histopathological changes were observed in gills including: Hyperplasia, loss of secondary lamellae, hemorrhage and congestion in primary and secondary lamellae, lamellar fusion, epithelial lifting in secondary lamellae, clubbing of secondary lamellae, telangiectases, increase in melanin pigments and numerous vacuoles in primary and secondary lamellae (in hyperoxia treatment). All these lesions may reduce gill functional surface of gaseous exchange, impairing respiratory function. Published